The diagnostic value of MRI-PDFF in hepatic steatosis of patients with metabolic dysfunction-associated steatotic liver disease: a systematic review and meta-analysis - Yue-Xia Zhang; Yan-Ping Feng; Cong-Lei You; Ling-Yun Zhang (BMC Gastroenterology)
Abstract Objective To evaluate the diagnostic efficacy of magnetic resonance imaging proton density fat fraction (MRI-PDFF) in assessing hepatic steatosis among patients with metabolic dysfunction-associated steatotic liver disease (MASLD) through systematic review and meta-analysis approaches. Methods Comprehensive searches were conducted across major public electronic databases, including PubMed, Web of Science, Cochrane Library, and Embase, to identify relevant studies that compared MRI-PDFF with liver biopsy in diagnosing steatosis in MASLD patients. Diagnostic accuracy was assessed using sensitivity, specificity, and the area under the curve (AUC) for differentiating various steatosis grades (S0 vs. S1-3; S0-1 vs. S2-3; S0-2 vs. S3). Results A total of 10 studies involving 939 MASLD patients were included in this meta-analysis. MRI-PDFF demonstrated robust diagnostic performance for steatosis grading, with sensitivity values ranging from 0.77 to 0.92 and specificity from 0.87 to 0.94. The AUC values were 0.98 (95% CI: 0.96–0.99) for S0 vs. S1-3, 0.92 (95% CI: 0.89–0.94) for S0-1 vs. S2-3, and 0.90 (95% CI: 0.87–0.93) for S0-2 vs. S3. Conclusion This meta-analysis suggests that MRI-PDFF is highly effective in grading steatosis in MASLD patients. Further validation through additional high-quality studies is warranted to consolidate these findings. Clinical trial number Not applicable.